Effect of aging on ultrasonic vocalizations and laryngeal sensorimotor neurons in rats - Basken, Jaime N. (2012)
While decline in vocal quality is prevalent in an aging population, the underlying neurobiological mechanisms contributing to age-related dysphonia are unknown and difficult to study in humans. Development of an animal model appears critical for investigating this issue. Using an established aging rat model, we evaluated if 50-kHz ultrasonic vocalizations in 10, 32-month-old (old) Fischer 344/Brown Norway rats differed from those in 10, 9-month-old (young adult) rats. The retrograde tracer, Cholera Toxin β, was injected to the thyroarytenoid muscle to determine if motoneuron loss in the nucleus ambiguus was associated with age. Results indicated that older rats had vocalizations with diminished acoustic complexity as demonstrated by reduced bandwidth, intensity, and peak frequency, and these changes were dependent on the type of 50-kHz vocalization. Simple calls of old rats had reduced bandwidth, peak frequency, and intensity while frequency-modulated calls of old rats had reduced bandwidth and intensity. Surprisingly, one call type, step calls, had increased duration in the aged rats. These findings reflect phonatory changes observed in older humans. We also found significant motoneuron loss in the nucleus ambiguus of aged rats, which suggests that motoneuron loss may be a contributing factor to decreased complexity and quality of ultrasonic vocalizations. These findings suggest that a rat ultrasonic phonation model may be useful for studying age-related changes in vocalization observed in humans.